The Riddle of the Sands - Childers, Erskine, 1870-1922 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Riddle of the Sands" by Erskine Childers is a novel written during the early 20th century. The story is a thrilling maritime adventure that blends elements of espionage and political intrigue, centered around the main character, Carruthers, who is drawn into a mysterious yachting trip with his old acquaintance, Davies. The narrative promises an exploration of both the physical waters of the Baltic Sea and the murky depths of national security. At the start of the tale, Carruthers is introduced as a somewhat disaffected young man, feeling out of place in the bustle of post-summer London, where his friends have abandoned the city for leisure. He receives an unexpected letter from Davies, inviting him to a yachting expedition in the Schleswig fiords. As Carruthers prepares for this journey, he reflects on his past encounters with Davies and his own sense of ennui. The beginning of the novel establishes both characters and sets up the mysterious ambiance that hints at deeper political currents, signaling that their trip could involve more than just leisurely yachting and shooting. The stage is set for an adventure that promises to blend personal growth with larger, unseen threats. (This is an automatically generated summary.)
Release date is 2000-10-01
Keywords: Sea stories; Great Britain -- History -- Invasions -- Fiction; Adventure stories; Spy stories; Sailing -- Fiction; Frisian Islands -- Fiction; Secret service -- Fiction; Alternative histories (Fiction)